Pengaruh Good Corporate Governance (GCG) dan Corporate Social Responsibility (CSR) terhadap Nilai Perusahaan - Indri Widjayanti; Ikfi Herowati Maghfiroh; Dien Noviany Rahmatika (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2024)
This study aims to re-examine the information that has existed in previous studies by proving that Good Corporate Governance and Corporate Social Responsibility have a significant influence on firm value. In this study using Systematic Literature Review (SLR) with a total of 41 previous journals have been taken from several websites such as Google Scholar, Semantic Scholar, Garuda Rujukan Digital, and Connected Papers. The number of previous journal publications on GCG and CSR is still fluctuating from 2020 - 2024. This research technique predominantly uses quantitative types. In collecting these research data, instruments that are widely used are mainly documentation techniques.